Semi-infinite moving crack in an orthotropic strip. (1st December 2017) - Basak, Prasanta; Mandal, S.C.
Abstract: The elastodynamic problem of semi-infinite moving crack in an orthotropic strip has been considered. Using Fourier transform technique the boundary value problem has been converted to standard Wiener–Hopf equation which has been solved to get the analytical expressions for the stress intensity factor and crack opening displacements. Finally the stress intensity factor and crack opening displacement have been plotted graphically against various parameters for different orthotropic media to show the effect of material orthotropy.